تحليل المستخلص الميثانولي لكالس نبات الحلبة Trigonella foenum graesum L. تحت الأجهاد المائي بتقنية الـ GC-MS/ Analysis of The Methanelli Extract of The Trigonella Toenum Graesum L Circuit. Under Water Stress with GC-MS technology (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
This study aimed to study the effect of water stress using different concentration of PEG (0,3,6,9%) to induce some chemical compound of Trigonella foenum graesum L. callus. The induction of callus has been done in vitro on MS media by using combinations of 2,4-D (0.5, 1, 1.5 mg/L) and BA (0.5, 1, 1.5 mg/L) to reach the best combination for the best highest callus fresh weight to choose it in the next experiment. The results showed that the combination (1mg/L  BA) +(1mg/L2,4-D) was the best combination to produce the highest fresh callus of Trigonella , which was used for induced callus.The solvent of methanol was used to extract the secondary metabolites from the inducsd callus under the stress condition. Gas Chromatography-Mass Spectrometry (GC-MS) technique was used to determine the secondary metabolite in the samples of methanol extracts of Trigonella callus, which revealed from the results that there were many compounds (about 17) for all plant samples